Fourth ventricle computed tomography indexes: standardisation and characteristics in neurocysticercosis - Svetlana Agapejev (Arquivos de Neuro-Psiquiatria)
OBJECTIVES: to propose standardisation of fourth ventricle dimensions and to study its characteristics in neurocysticercosis. METHOD: a control group (CG) constituted by 114 individuals with normal CT, and 80 patients with neurocysticercosis composed the group with neurocysticercosis (GN). Measures of the inner cranial diameter (Cr), fronto-polar distance between both lateral ventricles (FP), antero-posterior (AP) and latero-lateral (LL) fourth ventricle width based the standardisation of six indexes. RESULTS: AP/Cr, AP/LL and AP/FP were the more discriminative indexes, presenting in CG the mean values of 0.063, 0.267 and 0.582, respectively. The indexes in GN had values statistically higher than in CG. From GN, 51patients had increased indexes values above 2 standard deviation of the CG mean. AP/Ll was > or = 1 in 95% of patients with ventricular shunting and in 88% with depression. It also occurred in 73% patients with satisfactory follow-up and in everybody who died. CONCLUSION: AP/Cr, AP/LL and AP/FP may represent fourth ventricle dimensions.